Analisis Pengasutan Motor Induksi Menggunakan Softstarter dan Inverter - M Adam; P Harahap; B Oktrialdi; R Herlambang (Cered Indonesia Institute, 2021)
An induction motor that is started directly without using the starting method will draw 5 to 7 times the full load current and will only produce 1.5 to 2.5 times the full load torque. A large current will result in a voltage drop on the line so that it can interfere with other equipment connected to the line. For large-power motors, especially 3-phase induction motors, it will require a large starting current along with a large-power motor, so with motor power above 30 HP and above it is not recommended to start the motor directly without using the starting method. Some of the most commonly used starting methods are Direct on line (DOL), Star-Delta, Auto-transformer, Primary Resistance, Secondary Resistance, Inverter, and SoftStarter. Where the most widely used in the field is the DOL method, but this method still produces a large starting current. If it continues, it will shorten the life of the motor itself. This paper discusses the comparison between starting on softstarter and inverter on starting current. The results of the analysis of the starting current on the softstarter starting is 741A which is achieved in 9 seconds and the maximum torque produced by a 3-phase induction motor is 368.7 Nm. While the starting current on the inverter starting is 735A which is achieved in 13 seconds and the maximum torque produced by the 3-phase induction motor is 479.5 Nm